2014
DOI: 10.1007/s10096-014-2271-z
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant Gram-negative bacteria in solid organ transplant recipients with bacteremias

Abstract: Bloodstream infections (BSIs) remain as life-threatening complications and are associated with significant morbidity and mortality among solid organ transplant (SOT) recipients. Multidrug-resistant (MDR) Gram-negative bacteria can cause serious bacteremias in these recipients. Reviews have aimed to investigate MDR Gram-negative bacteremias; however, they were lacking in SOT recipients in the past. To better understand the characteristics of bacteremias due to MDR Gram-negative bacteria, optimize preventive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…In recent years, a reduction in the incidence of gram-negative (GN) in favor of gram-positive infections and higher rates of multidrug-resistant (MDR) infections in south-eastern versus north-western European regions have been observed [1]. Moreover, MDR GN infections have been recognized as 1 of the leading cause of mortality after solid organ transplantation [2][3][4][5], whereas their epidemiology and impact on patients with hematologic diseases and HSCT recipients have been less studied [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a reduction in the incidence of gram-negative (GN) in favor of gram-positive infections and higher rates of multidrug-resistant (MDR) infections in south-eastern versus north-western European regions have been observed [1]. Moreover, MDR GN infections have been recognized as 1 of the leading cause of mortality after solid organ transplantation [2][3][4][5], whereas their epidemiology and impact on patients with hematologic diseases and HSCT recipients have been less studied [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This change was evident among E. coli bloodstream isolates in one study, where resistance to fluoroquinolones and ampicillin antibiotics increased, between 1998 and 2007, from 0% to 44% ( P = .002) and from 50% to 76%, respectively . Multidrug‐resistant Enterobacteriaceae are also growing as a cause of infection in SOT patients and represent a global threat …”
Section: Introductionmentioning
confidence: 99%
“…3 Multidrug-resistant Enterobacteriaceae are also growing as a cause of infection in SOT patients and represent a global threat. 10 Understanding the nature of BSI among SOT recipients and its changing trends is paramount to implement the appropriate preventative and therapeutic strategies. Therefore, the aim of this study was to analyze the epidemiological and microbiological features of BSI among RTR in our center and to assess the potential impact of BSI on renal function.…”
Section: Introductionmentioning
confidence: 99%
“…18 This becomes important due to the high rate of MDR among gram-negative bacteria. 19 One study in China reported that MDR gram-negative bacteria were isolated from 56% of PTIs cases. 7 In line with the aforementioned study, MDR gram-negative bacteria were the most common pathogens in our study.…”
Section: Discussionmentioning
confidence: 99%